Quality assessment of market sample of khoa based ramdana lai - Bharti, Pragya; Kumar, Sanjeev; Kumar, Suryamani (Indian Journal of Dairy Science, 2021)
Khoa based Ramdana Lai (KBRL) is a popular traditional khoa based sweets of Bihar. It is prepared by khoa blending with ramdana, sugar and other additives. The present investigation was planned to assess the quality of KBRL samples from different location of Bihar. A total of 36 KBRL samples were collected from various locations of Bihar and were analyzed for their sensory, physico-chemical, microbial, textural and colour characteristics. The sensory scores of KBRL in terms of flavour, body and texture, colour and appearance and overall acceptability; the colour characteristics in terms of L*, a*, b* values; the textural characteristics in terms of hardness, springiness, cohesiveness, chewiness and gumminess and microbial quality measured in terms of TPC, yeast and molds and coliform count were found significantly (Pâ‰¤0.05) different among samples. The moisture, fat, protein, total carbohydrate and ash content of samples varied from 16.83 to 20.83%, 9.30 to 12.0%, 10.63 to 16.22%, 51.62 to 61.3% and 0.7 to 0.75%, respectively.